The general adaptation syndrome: Potential misapplications to resistance exercise - Buckner, S. L.; Mouser, J. G.; Dankel, S. J.; Jessee, M. B.; Mattocks, K. T.; Loenneke, J. P. (Journal of Science and Medicine in Sport, 2017)
Abstract: Within the resistance training literature, one of the most commonly cited tenets with respect to exercise programming is the "General Adaptation Syndrome" (GAS). The GAS is cited as a central theory behind the periodization of resistance exercise. However, after examining the original stress research by Hans Selye, the applications of GAS to resistance exercise may not be appropriate. Objectives: To examine the original work of Hans Selye, as well as the original papers through which the GAS was established as a central theory for periodized resistance exercise. Methods: We conducted a review of Selye`s work on the GAS, as well as the foundational papers through which this concept was applied to resistance exercise. Results/conclusions: The work of Hans Selye focused on the universal physiological stress responses noted upon exposure to toxic levels of a variety of pharmacological agents and stimuli. The extrapolations that have been made to resistance exercise appear loosely based on this concept and may not be an appropriate basis for application of the GAS to resistance exercise.